Databases for STEM success: lessons learned - Dietrich, Suzanne W.; Cunningham, Anna M.; Sandrin, Susannah K. (Frontiers in Education, 2024)
The ability to work with data to extract valuable information is a useful skill set, especially in STEM disciplines that produce large amounts of scientific data. This paper reports on the pedagogy and experience of incorporating fundamental database concepts into a STEM Success course, which included a hands-on project. Students worked in groups to design a database for existing tabular data available on the Web and then derived the data to populate the database using SQL queries. This paper reflects on the experience both from a pedagogical perspective as well as a student perspective, including qualitative code analysis of student feedback and survey results regarding attitudes of confidence using, interest in, and usefulness of databases.